A polynomial algorithm for convex quadratic optimization subject to linear inequalities - Chubanov, Sergei (Discrete Applied Mathematics, 2020)
This article proposes a polynomial-time algorithm for convex quadratic optimization subject to linear inequalities. The running time of the algorithm is polynomial in the binary size of the input data and in the logarithm of the reciprocal of the given accuracy.